2018
DOI: 10.1177/0003702818777772
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Cross-Section Stratifications of Icons Using Micro-Raman and Micro-Fourier Transform Infrared (FT-IR) Spectroscopy

Abstract: The cross-section stratifications of samples, which were removed from six icons, are studied using optical microscopy, micro-Raman spectroscopy, and micro-Fourier transform infrared (FT-IR) spectroscopy. The icons, dated from the 14th to 19th centuries, are prominent examples of Byzantine painting art and are attributed to different artistic workshops of ​​northern Greece. The following materials are identified in the cross-sections of the icon samples using micro-Raman spectroscopy: anhydrite; calcite; carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…The strong absorptions around 2,920 and 2,850 cm −1 (C─H stretching vibrations), along with the strong peak at 1708 cm −1 indicate the use of a natural resin (Figure 12), applied as a varnish layer. [ 9 ] The intense C─H absorptions in the upper part of the spectra fall in position similar to those of oil, suggesting the possibility that a lipid binder may also be present. This hypothesis is sustained by the carbonyl peak observed around 1730–1738 cm −1 and the peaks observed at 1164 and 720 cm −1 (Figure 9), these last ones ascribed to fatty acids present in oils.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strong absorptions around 2,920 and 2,850 cm −1 (C─H stretching vibrations), along with the strong peak at 1708 cm −1 indicate the use of a natural resin (Figure 12), applied as a varnish layer. [ 9 ] The intense C─H absorptions in the upper part of the spectra fall in position similar to those of oil, suggesting the possibility that a lipid binder may also be present. This hypothesis is sustained by the carbonyl peak observed around 1730–1738 cm −1 and the peaks observed at 1164 and 720 cm −1 (Figure 9), these last ones ascribed to fatty acids present in oils.…”
Section: Resultsmentioning
confidence: 99%
“…The use of anhydrite within the ground layer is not uncommon, [ 9 ] previous studies carried on Transylvanian icons showing a preference for calcium sulfate‐based grounds. [ 13–15 ] As shown in other studies, [ 9,20 ] various proportions of gypsum and anhydrite can be found within the ground layer, the high concentration of anhydrite being most probably linked with a poor lack of control of the calcination process of gypsum. [ 27,28 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the chromatic uniformity in remote phosphor structure is not ideal due to the shape of the encapsulation layer is hollow at the center. This leads to the uneven density of phosphor at different angles resulting in a yellow border around the emitted light of the device [20]. To enhance the overall performance of WLEDs, we applied the SiO2 particles which have shown positive results in our experiments regarding the color temperature consistency and light output.…”
Section: Introductionmentioning
confidence: 99%